COMPARISON BETWEEN PHYSICAL AND NON-PHYSICAL WORK ENVIRONMENT IN PBF X YOGYAKARTA - Ni Made Ayu Nila Septianingrum; Fitriana Yuliastuti (Universitas Muhammadiyah Magelang, 2020)
The convenience of working for employees is one of the keys to success for the company. If employees feel comfortable, their work productivity will increase and have a positive impact on the company. One factor that can provide comfort to employees is the work environment. The work environment is dividing into a physical work environment and a non-physical work environment. This study aims to determine the comparison of physical and non-physical work environments in PBF X in Yogyakarta. The method used is descriptive-analytic, with a cross-sectional approach and using saturated samples. Primary data were obtained by distributing questionnaires to all 25 PBF X employees. Data were processed using Microsoft Excel and presented in tables, diagrams, and descriptive (narrative) forms. The results obtained show a comparison of the mean value of the non-physical work environment is 3.0, and the mean value of the physical work environment is 2.8. The highest mean value in the non-physical work environment is about overtime salaries, while in the physical work environment, selecting paint colors at workplaces appropriate. The conclusion obtained that the non-physical work environment is more influential on respondents doing work in PBF X than the physical work environment. The company or PBF X needs to evaluate to create a comfortable physical work environment for employees so that the working atmosphere can increase company productivity